High-dose opioids in advanced cancer: use factors–retrospective study - Peng, Wanglian; Huang, Xufen; Zou, Ran; Chen, Qifang; Ding, Jialin; Jiang, Man; Yuan, Zhijun (BMJ supportive & palliative care, 2024)
ObjectivesTo evaluate factors associated with high-dose opioid use in patients with advanced cancer and examine the effect of high-dose opioid use on patients’ survival.MethodsThis study retrospectively searched the medical records of 416 patients with advanced cancer in a home-based hospice in central China. Age, sex, type of cancer, type of pain, the maximum oral morphine equivalent daily dose, type of opioid, preadmission oral morphine equivalent daily dose, lung cancer or not, bone metastases, opioid switch and survival time were assessed.ResultsThere were 416 subjects included from the 455 eligible participants (91.4%). 80 patients (19.2%) received high-dose opioids at home. Male (OR 2.471; 95% CI 1.054 to 5.792; p=0.037), preadmission morphine equivalent daily dose (OR 1.022; 95% CI 1.016 to 1.028; p=0.000) and the use of morphine at maximum morphine equivalent daily dose (OR 5.123; 95% CI 1.249 to 21.014; p=0.023) were positively predicted high-dose opioid use. No difference in survival was found when comparing the high-dose and very high-dose opioid use groups.ConclusionsMale home-based patients with advanced cancer who use morphine and have greater preadmission opioid doses should be aware of the necessity for high-dose opioid use. Regulated opioid use in adequate amounts does not shorten survival.